The welfare impact of land redistribution: Evidence from a Quasi-experimental initiative in Malawi - Mendola, M.; Simtowe, F. (Elsevier, 2015)
Land reform may be an effective means of reducing poverty in many developing countries where policy efforts have recently embraced a decentralized market-based approach to land redistribution. We use household panel data combined with a quasi-experimental program to assess the impact of a joint Malawi/World Bank land program on household well-being. Double difference and matching methods are used to address identification sources of bias. Results point to average positive effects on several productive outcomes of beneficiaries, while no effects are found with respect to access to social services. There is also evidence of heterogeneous effects by gender and inheritance systems.